Pengaruh Pelatihan Pertanian Organik The Learning Farm Indonesia terhadap Kompetensi Bertani Generasi Z (Jurnal Agribisnis Indonesia, 2023)
The research was aimed to determine the characteristics of the participants in The Learning Farm Indonesia training and analyze the effect of organic farming training by The Learning Farm Indonesia on Generation Z farming competence. The sample in this study was 1 (one) batch of participants in The Learning Farm Indonesia, namely youth aged 17-24 years (classified as in Generation Z), as many as 28 people. Characteristic data were analyzed using descriptive analysis. Meanwhile, competency and training data were analyzed by correlation analysis method using the SEM-PLS (Structural Equation Modeling - Partial Least Square) by utilizing the SmartPLS version 3 software application. The results showed that the characteristics of organic farming training participants of The Learning Farm Indonesia batch 41 were dominated by men, graduated from senior high school, and came from West Java. The training variables that influence the competency variables are training methods and training materials. The training method has an effect on knowledge with a p-value of 0.013. The training method has an effect on skills with a p-value of 0.025. The training material has an effect on skills with a p-value of 0.013. The training materials has an effect on attitudes with a p-value of 0.016. The training methods used by The Learning Farm Indonesia are lectures (lectures and discussions), video presentations, and action learning.